Special Economic Zones in USSR and Russian Federation (1980-2018) - D. S. Zheriborov (Научный диалог, 2019)
The question of the creation and functioning of special economic zones as territories with special legal status in the USSR and the Russian Federation in the period from the 1980s to the present time is considered. The authors pay attention to the history of development of special economic zones in different time intervals: from 1980 to 1990, from 1990 to 2000, from 2000 to 2005, from 2005 to 2016. The relevance of the article is due to the fact that the attraction of foreign investment is a priority issue for the leadership of any state, in particular, for the Russian Federation in different periods of history. It is noted that the importance of creating special economic zones is due to the need to attract foreign investment in the economy of the regions of the Russian Federation as one of the options for cooperation of the subjects of the Federation with foreign financial groups, since such economic interaction allows to solve many socially significant issues. The difficulties of creating free economic zones after the collapse of the Soviet Union in the conditions of political and economic instability are analyzed. It is shown that in the last few years the country’s leadership is taking measures for the effective development of these zones as a special tool for the successful development of the Russian economy.